Peripheral T-cell tolerance: the contribution of permissive T-cell migration into parenchymal tissues of the neonate - Alferink, Judith; Hämmerling, Günter J.; Arnold, Bernd (Immunological reviews, 2006)
Summary: T lymphocytes with self-destructive capacity are often found in healthy individuals, indicating efficient control mechanisms chat prevent chronic autoimmune deseases. Since naive T lymphocytes do not circulate through extralymphoid tissues the concept has emerged that peripheral T cells ignore tissue-,specific antigens unless they are presented by professional antigen-presenting cells in the lymphoid compartments. However, this view pays attention only to experiments performed in adult animals. This report reviews the evidence that tissues of neonatal mice, in contrast to adults, exhibit high accessibility for naive T cells, thereby allowing the direct contact with tissue-specific self-antigens on parenchymal cells during neonatal life and tolerance induction to such self-antigens. In mouse bone marrow chimeras generated at different ages, recent thymic emigrants were tolerized to a major histocompatibility class I antigen expressed on keratinocytes only during a neonatal period and not during adulthood. Blockade of T-cell migration neonatally prevented tolerance induction. The neonatally induced tolerance is maintained during adulthood, apparantly by a dominant regulatory mechanism. Thus, parenchymal cells and T-cell migration in the neonate contribute to the control of autoreactive T cells.
First published: 28 April 2006
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 16.02.2021